The Effect of Talent Management on Employee Satisfaction and Performance in Manufacturing Companies in Indonesia - Setyowati Subroto; Eko Sudarmanto; Moh Gifari sono (Westscience Press, 2024)
This study investigates the impact of talent management on employee satisfaction and performance in manufacturing companies in Indonesia. A quantitative approach was adopted, involving a sample of 150 employees from various firms. Data were collected using a structured questionnaire based on a Likert scale (1-5) and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results reveal that talent management significantly and positively influences both employee satisfaction and performance. Additionally, employee satisfaction mediates the relationship between talent management and performance, further enhancing the positive impact. These findings highlight the importance of comprehensive talent management strategies for improving employee outcomes in the manufacturing sector. Practical implications for human resource management and organizational competitiveness are discussed, with a focus on employee development, recognition, and performance improvement.